Wykorzystanie audiodeskrypcji w nauczaniu języka rosyjskiego na studiach filologicznych - Olechno-Wasiluk, Joanna (Neofilolog, 2024)
The article focuses on the possibilities of using audio description as a teaching aid in teaching Russian on university degree programmes. The author proposes a set of exercises for practical learning of Russian using the animated series Masha and the Bear. The structure of the proposed exercises includes several stages of student activities (including observation, language exercises, text editing, recording of a ready-made audio description), which makes it possible to adapt them to different levels of language proficiency of the learners. The proposed exercises do not focus only on verbal description itself, but also force the student to engage in in-depth analysis and reflection that requires reading the scene in a broader context, e.g. using the cultural background that can be seen while watching the series. Audio description is an attractive teaching aid, a tool that allows the simultaneous use of authentic material, such as the animation Masha and the Bear, and new technologies, including: applications for recording ready-made audio descriptions.